Self‐expanding metallic stent improves histopathological edema compared with transanal drainage tube for malignant colorectal obstruction. Issue 4 (26th January 2016) - Takeyama, Hiroshi; Kitani, Kotaro; Wakasa, Tomoko; Tsujie, Masanori; Fujiwara, Yoshinori; Mizuno, Shigeto; Yukawa, Masao; Ohta, Yoshio; Inoue, Masatoshi
Abstract : Background and Aim: To compare the usefulness of the self‐expanding metallic stent (SEMS) with that of the transanal drainage tube (TDT) and emergency surgery after failure of decompression (ESFD) in patients with malignant colonic obstruction (MCO), and to evaluate post‐decompression histopathological changes. Methods: From January 2010 to June 2015, 39 patients with MCO received SEMS, TDT, and ESFD. We evaluated the outcomes including success rates of placement, clinical outcomes after decompression, and histopathological findings of the resected specimens. Results: Technical success rates were 100% for SEMS and 78.9% for TDT. Clinical success rates were 100% for SEMS and 80.0% for TDT. Postoperative ileus was significantly less frequent after SEMS than after TDT ( P = 0.014). Histopathological edema grade was significantly lower for SEMS than for TDT and ESFD ( P < 0.0001). There was no significant difference between edema grade and duration of decompression in the TDT group ( P = 0.629), whereas all patients with SEMS were classified in a low edema grade (grade 0–2). Rate of stoma creation was significantly higher in patients with a high edema grade (grade 3) than in those with a low edema grade (grade 0–2) ( P = 0.003). There was no microscopic perforation in any group. Conclusion: Significantly greater resolution of histopathological edema was achieved after placement of SEMS than after placement of TDT. These findings provide an indication of favorable clinical outcomes of SEMS in comparison with TDT and ESFD.